Seasonal variability of turbidity, salinity, temperature and suspended chlorophyll in a strongly tidal sub-estuary: The Lynher Marine Conservation Zone. (15th November 2018) - Uncles, R.J.; Hooper, T.; Stephens, J.A.; Harris, C.
Abstract: The Lynher Estuary in Southwest England is a small, strongly tidal sub-estuary of the Tamar Estuary. It is a Site of Special Scientific Interest (SSSI), a Marine Conservation Zone (MCZ), a part of the Plymouth Sound and Estuaries Special Area of Conservation (SAC) and a Special Protection Area (SPA). Management of the Lynher SSSI and MCZ stipulates that good water quality and sediment quality should be maintained; as such, a good understanding of its responses to influences such as climate change and changes in agricultural practices within its catchment area is required. Observations of salinity, temperature, suspended particulate matter (SPM) concentrations, estuarine turbidity maximum (ETM) behaviour, and chlorophyll- a are presented for the Lynher over a 1-y period. The dataset provides important baseline information with which to identify future changes and guide management of the SSSI and MCZ as well as adding to our knowledge of estuarine systems. Salt intrusion is largely controlled by tides and runoff. A persistent ETM occurs that is closely associated with the freshwater-saltwater interface at high water (HW) and with a minimum in dissolved oxygen concentrations. HW depth-averaged ETM magnitudes are relatively low, less than 60 mg l −1 and typically 30 mg l −1 over the observation period. Larger tides and stronger flood-tide wind speeds lead to a stronger ETM. Tidal river HW SPM concentrations are intrinsically small (8 ± 8 mg l −1 during the observation period). Surface chlorophyll- a concentrations are low during winter (when they often peak near the ETM) and are much higher during spring and summer. Highlights: A persistent ETM occurs that is closely associated with the FSI at HW. Minimum DO occurs in the ETM region and decreases with increasing SPM. Larger tides and stronger flood-tide wind speeds lead to a stronger ETM. Higher SPM concentration at the Lynher mouth leads to a stronger ETM. Very low winter chlorophyll- a concentrations often peak near the ETM.